Pengaruh Model Pembelajaran Interaktif Setting Kooperatif Terhadap Hasil Belajar Pembelajaran Teknik Pemograman Mikroprosesor dan Mikrokontroler di SMK. - Yuliardi (JURNAL ILMIAH MAHASISWA, 2025)
This research aims to determine the influence of the cooperative setting interactive learning model on the learning outcomes of class XI students in the Microprocessor and Microcontroller Programming Engineering learning subjects at SMKS Muhammadiyah Banda Aceh. The approach used in research is quantitative, using experimental methods. The sample in this study was 12 people. To collect data, pre-test and post-test techniques were used. The research results show that there is an influence of the cooperative setting interactive learning model on the learning outcomes of class XI students in the Microprocessor and Microcontroller Programming Techniques learning subjects at SMKS Muhammadiyah Banda Aceh. This influence is marked by an increase in pre-test scores of 70 up to 80 in post-test. The hypothesis test shows a p score of = 0.005 < 0.05, so Ha is accepted, meaning that the interactive learning model of cooperative settings influences the learning outcomes of class XI students in the Microprocessor and Microcontroller Programming Engineering learning subjects at SMKS Muhammadiyah Banda Aceh. It can be concluded that interactive learning in a cooperative setting has been proven to be able to improve the learning outcomes of vocational school students.